2012
DOI: 10.1007/s00702-011-0759-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of hand preference in Parkinson’s disease

Abstract: This study focused on the difference between pre-morbid and current hand preference of patients with Parkinson's disease (PD). A survey instrument comprised items measuring pre-morbid and current hand preference and question related to the side of occurrence of initial symptoms. These questions were administered to 471 PD patients. The results show a significant change of pre-morbid right hand preference toward using the left when the side of PD onset was on the right hand and vice versa. Disease duration does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…That said both of the aforementioned groups differed from the RSA-PD group, where their laterality quotient was negative and thus indicative of superior left-hand performance. This extends the work by Štochl and colleagues [ 14 ] who noted a significant change from right- to left-hand preference when PD onset was on the right and vice versa. Štochl and colleagues' [ 14 ] methods were limited to a 7-item hand preference questionnaire, where premorbid hand preference was collected retrospectively; therefore, the current study provides additional support that PD motor symptom asymmetry does indeed influence handedness of individuals with PD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…That said both of the aforementioned groups differed from the RSA-PD group, where their laterality quotient was negative and thus indicative of superior left-hand performance. This extends the work by Štochl and colleagues [ 14 ] who noted a significant change from right- to left-hand preference when PD onset was on the right and vice versa. Štochl and colleagues' [ 14 ] methods were limited to a 7-item hand preference questionnaire, where premorbid hand preference was collected retrospectively; therefore, the current study provides additional support that PD motor symptom asymmetry does indeed influence handedness of individuals with PD.…”
Section: Discussionsupporting
confidence: 89%
“…Summarizing, results of the current study indicate that when the nonpreferred hand of right handers is affected by PD motor symptoms, superior preferred hand performance seen in H-OAs [ 22 , 23 ] is further exaggerated in tasks that require precision. Regardless of whether the task requires precision, or simply speed, when the preferred hand of right handers is affected, there is an evident shift to superior left-hand performance, which may inevitably manifest as a switch in hand preference [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hypothesis will need to be tested in future studies by checking whether the parallel and opposite relationship can be observed in a left-handed sample. Štochl, Croudace, Brožová, Klempíř, Roth, and Růžička (2012 ) showed there was a shift in the hemibody dominance if the preferred side was initially aff ected by the disease. Specifi cally, during the course of the disease patients begin to perform motor tasks with the unaff ected hemibody.…”
Section: Resultsmentioning
confidence: 99%
“…Change of hand preference while the disease progresses has also been reported. 36 This is an area to be investigated further, in different datasets and at different stages of the symptom progression. Another possible reason for the consistent worse performance by the left side was this side being always examined later per UPDRS form.…”
Section: Discussionmentioning
confidence: 99%